The Balaton as a Brand (Experiences of a Questionnaire Survey) - Erika Kiss; Nóra Baranyai Hegedűsné (DETUROPE)
The authors of this study examined the destination image of Lake Balaton which region is one of the top tourist destinations in Hungary. The empirical research was designed to obtain answers to two questions: whether the image of the region well recognizable and the much-discussed "Balaton-brand" could be formed? Research results indicate the different views about the region's image of the various stakeholders, the lack of effective communication between tourism operators and those professionals are not sufficiently aware of tourists’ views. The touristic region of Balaton has had an important role in the tourism of Hungary and the tourism supply of the region has undergone a huge transformation in the past period. In spite of these positive changes the main characteristic of the Balaton is still the shortness of its high season which is characterized by bathing in the lake. To enhance competitiveness, apart from broadening complex services it is necessary to introduce a clear Balaton brand and image on both internal and international markets.